(untitled) (World Bulletin of Management and Law, 2024)
The concept of digital investment is a new legal term in the field of law. New assets such as cryptocurrencies, tokens, Bitcoin are emerging .While digital investments are regulated in some countries, such as the United States, the United Kingdom, the European Union, Switzerland, and Singapore, they are not yet regulated in many countries. This article analyzes the types of digital investments and examines the laws of the countries that regulate them. It also discusses Howen’s test, which is used to determine whether digital values are investable. Problems like cybercrimes, territorial, security and protection problems, recognition of crypto-currency problems arising in the regulation of digital investments came to the world. After conducting some research and reviewing information in the article, solutions for improving this sphere were identified